2018
DOI: 10.3390/bios8010011
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Fuel Cells: Towards Self-Powered Implantable and Wearable Diagnostics

Abstract: With the rapid progress in nanotechnology and microengineering, point-of-care and personalised healthcare, based on wearable and implantable diagnostics, is becoming a reality. Enzymatic fuel cells (EFCs) hold great potential as a sustainable means to power such devices by using physiological fluids as the fuel. This review summarises the fundamental operation of EFCs and discusses the most recent advances for their use as implantable and wearable self-powered sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 87 publications
0
62
0
Order By: Relevance
“…150,159,164 Typical power densities for microuidic enzymatic biofuel cells have been reported to be several orders of magnitude higher than those achieved for microbial fuel cells, 159 with comparisons made for implantable devices. 165 Fuel cells implemented on lateral ow devices have been investigated 166 (Fig. 10C), as well as bacteria-driven paper-based biofuel batteries, 167,168 capable of powering an LED for up to 30 min.…”
Section: Biofuel Cellsmentioning
confidence: 99%
“…150,159,164 Typical power densities for microuidic enzymatic biofuel cells have been reported to be several orders of magnitude higher than those achieved for microbial fuel cells, 159 with comparisons made for implantable devices. 165 Fuel cells implemented on lateral ow devices have been investigated 166 (Fig. 10C), as well as bacteria-driven paper-based biofuel batteries, 167,168 capable of powering an LED for up to 30 min.…”
Section: Biofuel Cellsmentioning
confidence: 99%
“…In addition, according to the previous literature [9], the power density of the EFCs increased with the operated temperature until the temperature was raised to 45 • C to degrade enzymatic activities. At temperature above 45 • C, the power density decreased with the temperature.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, enzymatic biofuel cells (EFCs), which enable the conversion of chemical energy into electricity through electrochemical reactions of specific enzymes immobilized on electrodes, have attracted considerable attention. They have demonstrated potential for implantation into living organisms to generate electric power from body fluids, enabling them to function as a living battery for implantable sensors and medical devices [9]. In the past decades, several studies have reported the feasibility of such EFCs to generate electric power and drive electronic devices by implantation into different living organisms/species [10], such as rats [11][12][13], rabbits [14], cockroaches [15], clams [16], snails [17], lobsters [18], and insects [19].…”
Section: Introductionmentioning
confidence: 99%
“…As the growth stage is performed under nearly anaerobic conditions in which O 2 , the natural acceptor of GOx, is eliminated from the system through extensive N 2 purging, eqn (2) becomes favorable over eqn (3), and the PtCl 6 2À ions act as the sole acceptor of the FADH 2 electrons.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its attractive characteristics to bioelectronics, direct electron transfer (DET)-based enzymatic electrocatalysis has been a focus of intensive research in recent years. 1,2 The current realization of challenges and opportunities lying ahead in the eld of bioelectronics, [3][4][5][6] as well as rapid progress in the elds of material science and nanotechnology, [7][8][9] fuels the pursuing of novel direct charge transfer pathways to be implemented in third generation biosensors and enzymatic biofuel cells. DET is indeed benecial for such applications from various practical standpoints.…”
Section: Introductionmentioning
confidence: 99%